Structure/function interrelationships and illness insight in patients with schizophrenia: a multimodal MRI data fusion study: original paper - Otte, Marie-Luise; Schmitgen, Mike; Wolf, Nadine D.; Kubera, Katharina Maria; Calhoun, Vince D.; Fritze, Stefan; Geiger-Primo, Lena S.; Tost, Heike; Seidl, Ulrich; Meyer-Lindenberg, Andreas; Hirjak, Dusan; Wolf, Robert Christian (European archives of psychiatry and clinical neuroscience, 2023)
Illness insight in schizophrenia (SZ) has an important impact on treatment outcome, integration into society and can vary over the course of the disorder. To deal with and treat reduced or absent illness insight, we need to better understand its functional and structural correlates. Previous studies showed regionally abnormal brain volume in brain areas related to cognitive control and self-reference. However, little is known about associations between illness insight and structural and functional network strength in patients with SZ. This study employed a cross-sectional design to examine structural and functional differences between patients with SZ (n = 74) and healthy controls (n = 47) using structural and resting-state functional magnetic resonance imaging (MRI). Voxel-based morphometry was performed on structural data, and the amplitude of low frequency fluctuations (ALFF) was calculated for functional data. To investigate abnormal structure/function interrelationships and their association with illness insight, we used parallel independent component analysis (pICA). Significant group (SZ vs. HC) differences were detected in distinct structural and functional networks, predominantly comprising frontoparietal, temporal and cerebellar regions. Significant associations were found between illness insight and two distinct structural networks comprising frontoparietal (pre- and postcentral gyrus, inferior parietal lobule, thalamus, and precuneus) and posterior cortical regions (cuneus, precuneus, lingual, posterior cingulate, and middle occipital gyrus). Finally, we found a significant relationship between illness insight and functional network comprising temporal regions (superior temporal gyrus). This study suggests that aberrant structural and functional integrity of neural systems subserving cognitive control, memory and self-reference are tightly coupled to illness insight in SZ.
Online veröffentlicht: 20. Februar 2023
Gesehen am 15.02.2024